2019
DOI: 10.1103/physrevb.100.165416
|View full text |Cite
|
Sign up to set email alerts
|

Andreev reflection in ballistic normal metal/graphene/superconductor junctions

Abstract: We report the study of ballistic transport in normal metal/graphene/superconductor junctions in edge-contact geometry. While in the normal state, we have observed Fabry-Pérot resonances suggesting that charge carriers travel ballistically, the superconducting state shows that the Andreev reflection at the graphene/superconductor interface is affected by these interferences. Our experimental results in the superconducting state have been analyzed and explained with a modified Octavio-Tinkham-Blonder-Klapwijk mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…While this is unexpected, we note that without knowing exactly how many ABS channels are active in the JJ, it is not possible to extract a number for τ , as the measured anharmonicity coefficient only returns information on τ i = N τ . Additional experiments, such as extracting the transparency for each channel from multiple Andreev reflection via voltage-biased measurements [37][38][39][40], or direct measures of both E J and the anharmonicity coefficient in transmon qubits [41][42][43][44], would be required to draw further conclusions.…”
Section: Pure Mw Measurements Of the Josephson Nonlinearitymentioning
confidence: 99%
“…While this is unexpected, we note that without knowing exactly how many ABS channels are active in the JJ, it is not possible to extract a number for τ , as the measured anharmonicity coefficient only returns information on τ i = N τ . Additional experiments, such as extracting the transparency for each channel from multiple Andreev reflection via voltage-biased measurements [37][38][39][40], or direct measures of both E J and the anharmonicity coefficient in transmon qubits [41][42][43][44], would be required to draw further conclusions.…”
Section: Pure Mw Measurements Of the Josephson Nonlinearitymentioning
confidence: 99%
“…Graphene-superconductor interfaces exhibit very peculiar Andreev processes at low energy [40][41][42][43][44][45], and nonlocal processes have been predicted to occur under various conditions [46][47][48], including in the quantum Hall regime [28][29][30][31]. Thanks to the progress in device fabrication [49], graphene appears to be a clean and highly tunable two-dimensional material that couples very well to superconductors where a ballistic effect can be directly observed [50][51][52][53][54][55][56][57][58]. However, to our knowledge, very limited studies on nonlocal processes in clean graphene have been reported until now [59,60].…”
mentioning
confidence: 99%
“…[7] for the case of single walled carbon nanotube. We employ a modified Octavio-Tinkham-Blonder-Klapwijk (OTBK) model [47][48][49][50][51] along with a threeterminal beam splitter model to explain our experimental observation. The advantage of this implementation is that the Andreev reflection takes place locally at a single interface, and is not limited by contact spacing.…”
mentioning
confidence: 99%
“…We have used the dry transfer technique for the fabrication of h-BN/graphene/h-BN van der Waals heterostructure which is similar to the one described in Wang et al [34]. Edge contacts to the encapsulated graphene layer were established in a self-aligned manner as described in Kraft et al [39], and adapted for two different contact materials in Pandey et al [51]. Details of the devices are shown in the Supplemental Material [52].…”
mentioning
confidence: 99%
See 1 more Smart Citation